Infection Sources and Klebsiella pneumoniae Antibiotic Susceptibilities in Endogenous Klebsiella Endophthalmitis - Kuan-Jen Chen; Yen-Po Chen; Yi-Hsing Chen; Laura Liu; Nan-Kai Wang; An-Ning Chao; Wei-Chi Wu; Yih-Shiou Hwang; Hung-Da Chou; Eugene Yu-Chuan Kang; Yen-Ting Chen; Ming-Hui Sun; et al. (MDPI AG, 2022)
Endogenous endophthalmitis is an uncommon intraocular infection with potentially devastating consequences on vision. Klebsiella pneumoniae is highly prevalent in East Asian countries, with an increasing incidence recently worldwide. This retrospective study investigates infection sources and antibiotic susceptibilities of K. pneumoniae in patients with endogenous K. pneumoniae endophthalmitis (EKE) in Northern Taiwan. One hundred and fifty-seven patients with EKE were reviewed between January 1996 and April 2019. Pyogenic liver abscess (120/157, 76.4%) was the most common infection source, followed by pneumonia (13, 8.3%), urinary tract infection (7, 4.5%), and intravenous drug use (4, 2.5%). Bilateral involvement was identified in 12.1% (19/157) of patients, especially in patients with pyogenic liver abscess (16/120, 13.3%), pneumonia (2/13, 15.4%), and urinary tract infection (1/7, 14.3%). The antibiotic susceptibility rates were 98.1%, 92.5%, 97.5%, 96.8%, 100%, 99.3%, and 100% for amikacin, cefuroxime, ceftazidime, ceftriaxone, carbapenems, ciprofloxacin, and levofloxacin, respectively. Four extended-spectrum β-lactamase-producing multidrug-resistant (MDR) K. pneumoniae isolates were identified. In conclusion, pyogenic liver abscess was the major infection source in EKE. In addition, K. pneumoniae was still highly susceptible to ceftazidime and amikacin, and the MDR K. pneumoniae isolates were not common in EKE.